Unexplained Fatigue in an Otherwise Healthy Man Linked to Kikuchi-Fujimoto Disease, A Case Report - Pant, Vivek; Pradhan, Santosh; Sharma, Vijay Kumar (Nepalese Medical Journal, 2021)
Kikuchi histiocytic necrotizing lymphadenitis is a benign and self-limited illness usually characterized by cervical lymphadenopathy and fever. We present a case of a 42-year male who complained of extreme fatigue for 2 weeks. On laboratory workup, he had leucopenia and thrombocytopenia with normal peripheral blood and bone marrow examination. The radiological investigation revealed multiple enlarged lymph nodes in the left axilla and left supraclavicular region. The subsequent excisional biopsy of the axillary node clinched the diagnosis of Kikuchi- Fujimoto disease. The patient was completely recovered and laboratory parameters were normal with supportive treatment. Kikuchi- Fujimoto disease should be considered in patients with unexplained fatigue with lymphadenopathy and early biopsy prevents unnecessary investigations as well as potentially harmful treatments.